Login
Register
Made in Bihar, India
Toggle navigation
Home
About Us
Courses
FAQ
Contact Us
Home
About Us
Courses
FAQ
Contact Us
Prove that: (A+2B).(2A-3B) = 2A^2 + ABcos(theta) -6B^2
Sahay Sir
>
Question Answers
>
Prove that: (A+2B).(2A-3B) = 2A^2 + ABcos(theta) -6B^2
Prove that: (A + 2B).(2A – 3B) = 2A^2 + AB cos (theta) – 6B^2
27
Aug
Prove that: (A + 2B).(2A – 3B) = 2A^2 + AB cos (theta) – 6B^2 Prove that: (A+2B).(2A-3B) = 2A^2 + ABcos(theta) -6B^2 August 27, 2020 Category: Uncategorised (JEE Advanced Physics by BM Sharma + GMP Solutions) ,
Posted in:
Uncategorised (JEE Advanced Physics by BM Sharma + GMP Solutions)
,
Tags:
Prove that: (A+2B).(2A-3B) = 2A^2 + ABcos(theta) -6B^2
,
Search